Nurse-Administered Propofol Continuous Infusion Sedation: A New Paradigm for Gastrointestinal Procedural Sedation. (8th April 2021) - Lin, Otto S.; La Selva, Danielle; Kozarek, Richard A.; Weigel, Wade; Beecher, Ryan; Gluck, Michael; Chiorean, Michael; Boden, Elisa; Venu, Nanda; Krishnamoorthi, Rajesh; Larsen, Michael; Ross, Andrew
Abstract : INTRODUCTION: Nurse-Administered Propofol Continuous Infusion Sedation (NAPCIS) is a new nonanesthesia propofol delivery method for gastrointestinal endoscopy. NAPCIS is adopted from the computer-assisted propofol sedation (CAPS) protocol. We evaluated the effectiveness, efficiency, and safety of NAPCIS in low-risk subjects. METHODS: Between December 2016 and July 2017, patients who underwent esophagogastroduodenoscopy or colonoscopy with NAPCIS at our center were compared against 2 historical control groups of similar patients who had undergone procedures with CAPS or midazolam and fentanyl (MF) sedation. RESULTS: The mean age of the NAPCIS cohort (N = 3, 331) was 55.2 years (45.8% male) for 945 esophagogastroduodenoscopies and 57.8 years (48.7% male) for 2, 386 colonoscopies. The procedural success rates with NAPCIS were high (99.1%–99.2%) and similar to those seen in 3, 603 CAPS (98.8%–99.0%) and 3, 809 MF (99.0%–99.3%) controls. NAPCIS recovery times were shorter than both CAPS and MF (24.8 vs 31.7 and 52.4 minutes, respectively; P < 0.001). On arrival at the recovery unit, 86.6% of NAPCIS subjects were recorded as "Awake" compared with 82.8% of CAPS and 40.8% of MF controls ( P < 0.001). Validated clinician and patient satisfaction scores were generally higher for NAPCIS compared with CAPS and MF subjects. For NAPCIS, there were only 4 cases of oxygen desaturation requiring transient mask ventilation and no serious sedation-related complications. These low complication rates were similar to those seen with CAPS (8 cases of mask ventilation) and MF (3 cases). DISCUSSION: NAPCIS seems to be a safe, effective, and efficient means of providing moderate sedation for upper endoscopy and colonoscopy in low-risk patients.